Islam dan Pembangunan Manusia Di Era Globalisasi - Bukhari, As’ad (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2018)
In the globalization era, people are increasingly competitive and increasing their ability to become productive human beings. Human development is the main thing in doing change and progress in life. In the discussion Human development in the era of globalization which is a world program through the unity of nations is inseparable from the study of Islam. So that Islam as a religion can enter to become a very important discussion in development issues of course. National development becomes the main task of the government from the regional level to the province, thus providing human resources as a form of mover and its managers. Policies on human resource development always experience dynamics and perkembangnnya in terms of sociology, anthropology and culture. Islam as the majority religion in Indonesia becomes a determinant and has a major influence on development issues nationally. Islam and human development in the era of globalization becomes the most important thing to build Indonesia into a culture, character and progress. Thus the development process becomes the main part to reconstruct the infrastructure, human, network and every aspect. Construction in religious thought that is the study of Islamic thought in the development process becomes the goal for tercipatanya development in the era of globalization. It is also a form of advancing the society and mindset of a digitally literate man and aware of science, technology, development and life in the era of globalization in the form of international relations.Keywords: Construction OfÂ Islamic, Human Development